Implementing AI Replika in higher education speaking classes: Benefits and challenges - Girindra Putri Dewi Saraswati; Alief Noor Farida; Yuliati Yuliati (ELT Forum: Journal of English Language Teaching, 2023)
The demand from students for native English speakers as interlocutors justifies the importance of this research. Because of the nation's location and financial constraints, speaking course participants are said to lack experience speaking with native speakers. Gaining a tangible understanding of how AI Replika can be used to replace native speakers’ role in becoming students’ source of native speaker is the anticipated outcome of this project. This study investigates the benefits and difficulties of using AI Replika in speaking classes. With the help of AI Replika, students may practice speaking English in real time or directly with the use of artificial intelligence. The features used by students can be either chatbot or speaking robot. This study used a descriptive qualitative methodology. A case study methodology is applied. Interviewing and participant observation were employed as data collection methods. Three basic types of triangulations are used in data validity techniques: theoretical, methodological, and source data triangulation. Based on the results, it shows that AI replica can be used as the alternative on the absence of native speaker in practicing speaking. However, the role of teachers in the classroom still cannot be replaced by the AI. Students feel that although AI Replika brings benefit for them to practice speaking before class, however, they still need teachers to explain the context of the speaking content. Students also feel that the AI Replika brings more literal meaning of an idea rather than able to understand the cultural meaning behind the talk. In the end, AI technology can improve language acquisition with a well-balanced approach, but real native speaker presence for more humanist approach is still needed.